Boosting Photocatalytic Hydrogen Evolution of 2D Multinary Copper Chalcogenide Nanocrystals Enabled by Tuning Metal Precursors - Li, Yu; Liu, Zheming; Zhang, Liya; Chen, Jie; Wang, Shuaibing; Ma, Mengmeng; Yin, Zhe; Man, Zhongwei; Yi, Ding; Wang, Zhijie; Tang, Aiwei (Small (Weinheim an der Bergstrasse, Germany), 2025)
It is challenging to clarify modulation mechanisms and structure‐activity relationships in the ion‐regulation engineering of multinary copper chalcogenide nanocrystals (NCs) for solar‐to‐hydrogen conversion. Herein, quaternary 2D Cu–In–Zn–S NCs are fabricated using various indium precursors to expose a high proportion of (0002) crystal facets that are positively correlated with their photocatalytic activities. Theoretical calculations demonstrate that the specific adsorption of anions on the crystal facets significantly influences their anisotropic growth and, in turn, photocatalytic performance. Furthermore, 2D Cu–In–Ga–Zn–S (CIGZS) NCs are prepared by partially or completely substituting In3+ with Ga3+ cations. As the Ga3⁺ content gradually increases, the resulting photocatalytic activities follow a bell‐shaped trend. The initial increase is attributed to a synergistic effect of optimized catalytic ability and a stronger electron driving force introduced by Ga3⁺ incorporation. However, excessive Ga3⁺ substitution widens the bandgap, reducing light absorption and conversion, ultimately leading to a decline in photocatalytic activities. Notably, the photocatalytic activity of Cu–Ga–Zn–S NCs with the highest hydrogen evolution rate of 1566.8 µmol g−1 h−1 under visible light surpassed those of all In‐based NCs due to enhanced electron‐hole separation efficiency and highly effective active sites. This study provides valuable insights into the rational design of multinary copper‐based photocatalysts for solar‐driven hydrogen production. This study prepares 2D Cu−In−Zn−S nanocrystals (NCs) to achieve a high exposure proportion of (0002) crystal facets that are positively correlated with their photocatalytic activities. Then, 2D Cu–In–Ga–Zn–S (CIGZS) NCs are synthesized by partially or completely substituting In3+ with Ga3+ cations. Results indicate that CGZS NCs possess more advantages than CIZS NCs in solar‐to‐hydrogen conversion.